Mobile-Assisted Language Learning (MALL) in EFL Classroom: Examining Its Contribution to Students’ Foreign Language Acquisition Process - Sutrisna, I Putu Edi (Universitas Pendidikan Ganesha, 2025)
This study investigates the role of Mobile-Assisted Language Learning (MALL) in English as a Foreign Language (EFL) acquisition among university students in Bali. Variations in students’ language proficiency indicate the influence of mobile technology in the learning process. Using an Interpretative Phenomenological Analysis (IPA) approach, the study explores how students interact with MALL, which language skills are enhanced, and the challenges and opportunities they encounter. Findings reveal that students engaged with MALL autonomously through platforms like YouTube, TikTok, Instagram, and Duolingo, integrating English learning into their daily lives. MALL contributed most significantly to vocabulary and listening skills, with improvements in speaking, reading, and grammar emerging through incidental and repeated exposure. The study supports Nation’s vocabulary framework (Nation, 2001), Krashen’s Input Hypothesis (Krashen, 1982), and Mayer’s Cognitive Theory of Multimedia Learning (Mayer, 2024). Students appreciated MALL’s flexibility, authentic input, and low-pressure environment, which promoted motivation and self-regulated learning. The implications suggest that MALL can serve as a more flexible, contextual, and learner-centered model for language education in the digital era. Integrating MALL into formal curricula can enhance learner autonomy, foster intrinsic motivation, and expand access to authentic learning materialspromoting self-directed and technologically adaptive language learners.